Silicon MEMS bistable electromagnetic vibration energy harvester using double-layer micro-coils. (November 2015) - Podder, P; Constantinou, P; Mallick, D; Roy, S
Abstract: This work reports the development of a MEMS bistable electromagnetic vibrational energy harvester (EMVEH) consisting of a silicon-on-insulator (SOI) spiral spring, double layer micro-coils and miniaturized NdFeB magnets. Furthermore, with respect to the spiral silicon spring based VEH, four different square micro-coil topologies with different copper track width and number of turns have been investigated to determine the optimal coil dimensions. The micro-generator with the optimal micro-coil generated 0.68 micro-watt load power over an optimum resistive load at 0.1g acceleration, leading to normalized power density of 3.5 kg.s/m 3 . At higher accelerations the load power increased, and the vibrating magnet collides with the planar micro-coil producing wider bandwidth. Simulation results show that a substantially wider bandwidth could be achieved in the same device by introducing bistable nonlinearity through a repulsive configuration between the moving and fixed permanent magnets.